PROFESSIONAL COMMUNICATIVE COMPETENCE OF THE FUTURE DOCUMENT CONTROL SPECIALISTS: CONTENT AND STRUCTURE - Оксана Тур (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article defines the main aim of the professional education on the present stage of the society development. Cognitive and competential pedagogical approaches are characterized. The notions of "competence" and "professional communicative competence" are defined. The article distinguishes the structure of the professional communicative competence which includes professional reflection, social perception, linguistic component and functional components such as informational, behavioural and motivational. Reflective, active and sociocultural levels of the development of the professional communicative competence of the future document control specialists are determined.